2011
DOI: 10.1177/1362361311427154
|View full text |Cite
|
Sign up to set email alerts
|

Advancing paternal age and simplex autism

Abstract: De novo events appear more common in female and simplex autism spectrum disorder (ASD) cases and may underlie greater ASD risk in older fathers' offspring. This study examined whether advancing paternal age predicts an increase in simplex (n = 90) versus multiplex ASD cases (n = 587) in 677 participants (340 families). Whether or not controlling for maternal age, results support a significant interaction of linear paternal age and sex of the child on simplex family type. Female ASD cases were significantly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…The sex-specific neuroanatomy discovered here for high-functioning adults with autism are in line with the growing evidence of sex-specific biological profiles for the high-functioning subgroup at the levels of serum proteomics (Schwarz et al , 2011; Ramsey et al , 2012), sex steroid hormones and anthropometry (Ruta et al , 2011; Bejerot et al , 2012), and for the whole autism spectrum at the levels of genetics (Gilman et al , 2011; Puleo et al , 2012; Szatmari et al , 2012), transcriptomics (Kong et al , 2012) and early brain overgrowth (Sparks et al , 2002; Bloss and Courchesne, 2007; Schumann et al , 2009, 2010; Nordahl et al , 2011). In sum, high-functioning males and females with autism, though diagnosed by the same behavioural criteria, differ in aspects of neuroanatomy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The sex-specific neuroanatomy discovered here for high-functioning adults with autism are in line with the growing evidence of sex-specific biological profiles for the high-functioning subgroup at the levels of serum proteomics (Schwarz et al , 2011; Ramsey et al , 2012), sex steroid hormones and anthropometry (Ruta et al , 2011; Bejerot et al , 2012), and for the whole autism spectrum at the levels of genetics (Gilman et al , 2011; Puleo et al , 2012; Szatmari et al , 2012), transcriptomics (Kong et al , 2012) and early brain overgrowth (Sparks et al , 2002; Bloss and Courchesne, 2007; Schumann et al , 2009, 2010; Nordahl et al , 2011). In sum, high-functioning males and females with autism, though diagnosed by the same behavioural criteria, differ in aspects of neuroanatomy.…”
Section: Discussionsupporting
confidence: 84%
“…Although some studies report no sex differences in cardinal autistic behavioural characteristics after controlling for IQ (Tsai and Beisler, 1983; Pilowsky et al , 1998; Holtmann et al , 2007; Solomon et al , 2012), others do (McLennan et al , 1993; Carter et al , 2007; Hartley and Sikora, 2009; Lai et al , 2011; Mandy et al , 2012). Females with autism have also been found to differ from males with autism at the levels of cognition (Carter et al , 2007; Bolte et al , 2011; Lemon et al , 2011; Lai et al , 2012 b ), proteomics (Schwarz et al , 2011; Ramsey et al , 2012), hormones (Ruta et al , 2011; Bejerot et al , 2012), genetics (Gilman et al , 2011; Puleo et al , 2012; Szatmari et al , 2012), transcriptomics (Kong et al , 2012), and early brain overgrowth (Sparks et al , 2002; Bloss and Courchesne, 2007; Schumann et al , 2009, 2010; Nordahl et al , 2011). Structural neuroimaging studies focusing on females (Craig et al , 2007; Calderoni et al , 2012) also reveal little overlap of atypical brain areas compared with those found in meta-analyses of predominantly male samples (Radua et al , 2011; Via et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the possibility that higher maternal age is a greater risk factor for male than female offspring. Intriguingly, a converse pattern has been observed for paternal age, with paternal age appearing to pose the greatest risk for female offspring (Croen et al, 2007;Reichenberg et al, 2006), in particular simplex autism (Puleo et al, 2012). However, a recent large-scale study failed to find sexmoderating effect on risks for offspring ASC associated with increased parental ages (Sandin et al, 2015).…”
Section: Maternal Agementioning
confidence: 99%
“…Despite evidence for a likely involvement of de novo and environmental or epigenetic risk factors, including maternal antibodies 16 or stress during pregnancy 17 and paternal age, 18,19 we contend that coding variations contribute substantially to the heritability of ASD and can be successfully detected and assembled into connected pathways with GWAS—if the experimental design, the primary outcome, the statistical methods used, and the decision rules applied were better targeted toward the particulars of non-randomized studies of common diseases. With u -statistics for genetically structured wide-locus data comprising several neighboring SNPs (ÎŒGWAS) addressing the former two conditions, we have recently confirmed axonal guidance and Ca 2+ signaling as key pathways in childhood absence epilepsy (CAE) 20 from 185 cases and publicly available controls only.…”
Section: Introductionmentioning
confidence: 96%